E-069 Super-selective fistula point coil embolization for carotid-cavernous arteriovenous fistula. (22nd July 2019) - Majidi, S; Singh, I; Fifi, J
Abstract : Background/Purpose: Endovascular treatment of carotid-cavernous fistula (CCF) has evolved over the past two decades from using detachable balloons to Onyx and coil embolization. Nowadays, transvenous coil embolization is the mainstay of CCF management. Obliteration of the cavernous sinus with coils or liquid embolic agent can be time consuming and costly and potentially lead to cranial nerve injury. We report technical aspects and clinical outcome of a transvenous super-selective fistula point coil embolization. Methods: We retrospectively reviewed consecutive patients with CCF who were treated by a single operator in our institution from January 2016 to December 2018. Patients' demographics, type of CCF, endovascular embolization technique and clinical and angiographic outcome were analyzed. Super-selective fistula point embolization is a technique by which microcatheter exploration allows for definition of the fistula location within the cavernous sinus and targeted coiling at this point. Results: A total of 11 patients were identified. All patients had type D dural arteriovenous CCF. Fifty percent of the patients were female. The mean age (±SD) of the patients were 61±13 years. All patients were treated with transvenous super-selective coil embolization of the fistula point (figure-1). The inferior petrosal sinus was used to access the fistula point at the cavernous sinus and superior ophthalmic vein junction in 9 patients. In the remaining 2 patients, the facial vein was used to access the fistula point. Ten patients had complete fistula obliteration in the final angiographic run at the end of the embolization procedure. One patient had small residual fistula which was completely obliterated by further super-selective coiling during follow up angiography. No procedure related morbidity or mortality was observed. All 11 patients had complete resolution of their clinical symptoms. A total of 7 patients had follow up cerebral angiography and 3 patients had follow up MRI/MRA at the 6 to 12 month timepoint which were all indicative of complete obliteration of the CCF. Conclusions: Super-selective transvenous coil embolization of a focal fistula point in patients with CCF is safe and feasible and is associated with excellent durable clinical and angiographic outcome. Disclosures: S. Majidi: None. I. Singh: None. J. Fifi: None.